Neurodegenerative Marine Algae Bioactive Compounds: A Viable Cure to Treat Amyotrophic Lateral Sclerosis (ALS): A Review - Ayyandurai Mani; Mathiyazhagan Narayanan; V. Rajinikanth (Dubai Medical Journal)
Introduction: Amyotrophic lateral sclerosis (ALS), a neurodegenerative disease that causes muscle weakness, paralysis, and death, develops when motor neurons begin to die. There are few proven treatments for ALS, and because the disease is incurable, the exact cause is unknown, making it a devastating condition. According to recent research, marine algae may contain bioactive substances that can be used to treat ALS.